A study of neutral currents in three-phase distribution network with non-linear loads - Diana Geruka (School of Electrical Systems Engineering, 2009)
Neutral currents are produce by non-linear load. Excessive neutral current can caused a lot of problem to the system. Beside, the third harmonic is the predominant component on the neutral. The total harmonic distortion divided into two which are harmonic current distortion and harmonic voltage distortion. In other hand, the load on a three-phase system can be a balanced or unbalanced load. So, the mathematical for both of its different and the amount of neutral current can be determine. The nonlinear loads are loads which the load current is not proportional to voltage. The simulation which is use PSPICE is to prove the result of simulation is same with the theory.